2022
DOI: 10.1007/s13668-022-00413-4
|View full text |Cite
|
Sign up to set email alerts
|

Interrelations Between Food Form, Texture, and Matrix Influence Energy Intake and Metabolic Responses

Abstract: Purpose of Review Nutrition often focuses on food composition, yet differences in food form, texture, and matrix influence energy intake and metabolism. This review outlines how these attributes of food impact oral processing, energy intake, and metabolism. Recent Findings Food form has a well-established impact on intake, where liquids are consumed more than solids and semi-solids. For s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 85 publications
0
29
0
Order By: Relevance
“…People do not eat individual nutrients, but instead consume foods combined as meals, consisting of a mixture of nutrients of different bioavailabilities. The bioavailability of these nutrients may differ by food matrix and interaction between food components [ 14 ]. Moreover, it has been shown that selected dietary habits usually cluster together so that, for example, people with high intakes of soda and sweet products tend to eat more snacks and fried potatoes [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…People do not eat individual nutrients, but instead consume foods combined as meals, consisting of a mixture of nutrients of different bioavailabilities. The bioavailability of these nutrients may differ by food matrix and interaction between food components [ 14 ]. Moreover, it has been shown that selected dietary habits usually cluster together so that, for example, people with high intakes of soda and sweet products tend to eat more snacks and fried potatoes [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies [ 29 , 30 ] have reported an increase in overall liking of foods with higher hardness, whereas others [ 31 , 32 , 33 ] have found no effect of hardness on acceptability. Increasing food hardness may be effective at slowing energy intake [ 34 ], and therefore, HP hydrogels may be useful for enhancing satiety and combating obesity.…”
Section: Resultsmentioning
confidence: 99%
“…There is a need to better inform the consumer about the processing steps needed and explain why certain ingredients are needed to improve food quality or safety. Consumers should also be aware that food processing could be used to increase the health status of a product, such as by nutritional fortifications or by designing foods in a way that prevents overconsumption [ 50 ]. It may help to give consumers more transparency on food formulation and food processing to restore their trust in the food industry [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Nutri-Score uses nutrient composition to judge the healthiness of food. There is growing evidence that the healthiness of food is not only determined by the sum of its nutrients but also depends on the food form and its microstructure [ 50 , 51 ] and possibly the use of non-nutritive additions in food processing [ 52 ]. To date, there is no gold standard to judge the healthiness of foods.…”
Section: Discussionmentioning
confidence: 99%